International socialism : . International Socialism
Since 2nd series subtitled: Theoretical quarterly of the Socialist workers party. - Split into:...2nd series, and: Socialist review. Monthly members organ...(ZK 40791). - Continues: International discussion bulletin. Socialist workers party (ZK 30590).